Primary Lung Dendritic Cell Cultures to Assess Efficacy of Spectinamide-1599 Against Intracellular Mycobacterium tuberculosis - Santos, Karen; Lukka, Pradeep B.; Grzegorzewicz, Anne; Jackson, Mary; Trivedi, Ashit; Pavan, Fernando; Chorilli, Marlus; Braunstein, Miriam; Hickey, Anthony; Meibohm, Bernd; Gonzalez-Juarrero, Mercedes (Frontiers in Microbiology, 2018)
There is an urgent need to treat tuberculosis (TB) quickly, effectively and without side effects. Mycobacterium tuberculosis (Mtb), the causative organism of TB, can survive for long periods of time within macrophages and dendritic cells and these intracellular bacilli are difficult to eliminate with current drug regimens. It is well established that Mtb responds differentially to drug treatment depending on its extracellular and intracellular location and replicative state. In this study, we isolated and cultured lung derived dendritic cells to be used as a screening system for drug efficacy against intracellular mycobacteria. Using mono- or combination drug treatments, we studied the action of spectinamide-1599 and pyrazinamide (antibiotics targeting slow-growing bacilli) in killing bacilli located within lung derived dendritic cells. Furthermore, because IFN-γ is an essential cytokine produced in response to Mtb infection and present during TB chemotherapy, we also assessed the efficacy of these drugs in the presence and absence of IFN-γ. Our results demonstrated that monotherapy with either spectinamide-1599 or pyrazinamide can reduce the intracellular bacterial burden by more than 99.9%. Even more impressive is that when TB infected lung derived dendritic cells are treated with spectinamide-1599 and pyrazinamide in combination with IFN-γ a strong synergistic effect was observed, which reduced the intracellular burden below the limit of detection. We concluded that IFN-γ activation of lung derived dendritic cells is essential for synergy between spectinamide-1599 and pyrazinamide.